2014
DOI: 10.1007/s10725-014-0008-8
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of salt stress in germination of Vigna radiata L. by two halotolerant Bacilli sp. isolated from saline habitats of Gujarat

Abstract: Fifty halotolerant bacterial strains were isolated from the alkaline saline soil from the Ajod village of Vadodara district of Gujarat. All strains grew well in media supplemented with 5 % NaCl, but two strains (BR5 and BN7) could grow even at 18 % NaCl concentration. These two strains were characterized for their plant growth promoting characteristics. Both the strains were able to solubilize significant amount of phosphate and produce IAA. Both the strains also showed nitrogen fixing, siderophore production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…To alleviate the soil salinity stress in diverse crop plants, several studies have demonstrated the efficiency of plant inoculation with PGPRs (Singh et al 2015;Bharti et al 2016;Singh and Jha 2017;Sapre et al 2018). An important factor to be considered when looking for new isolates is to screen them from environmental conditions for which they would be used (Pr ıncipe et al 2007). In natural ecosystems, rhizosphere of halophytes is then suitable to screen for bacteria with high capacities to support and promote plant growth (S aenz-Mata et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To alleviate the soil salinity stress in diverse crop plants, several studies have demonstrated the efficiency of plant inoculation with PGPRs (Singh et al 2015;Bharti et al 2016;Singh and Jha 2017;Sapre et al 2018). An important factor to be considered when looking for new isolates is to screen them from environmental conditions for which they would be used (Pr ıncipe et al 2007). In natural ecosystems, rhizosphere of halophytes is then suitable to screen for bacteria with high capacities to support and promote plant growth (S aenz-Mata et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the MLR6 isolate displayed also indirect plant promotion traits such as NH 3 + and chitinase production. The above-mentioned traits were reported for their role in alleviating salt stress (Goswami et al 2014;Patel et al 2015;Li et al 2016;Sapre et al 2018) and their implication in the plant growth. In our study, plant height and shoot fresh weight decreased in control plants under NaCl stress but A. thaliana inoculation with MLR6 increased significantly the plant growth parameters under normal as well as under saline stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…) and secondary metabolites against phytopathogens (Ongena and Jacques ; Lugtenberg and Kamilova ; Patel et al . ). Indeed, halotolerant bacteria have been found to be capable of producing different kinds of surface‐active lipopeptides, which had broad spectrum antimicrobial activities (Roongsawang et al .…”
Section: Introductionmentioning
confidence: 97%
“…Particular attention has been paid on halotolerant bacteria, which inhabit hyper saline environments and have been shown to reduce salt stress on various plants (Patel et al . ; Wang et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…The mung bean (Vigna radiata) is salinity-sensitive and suffers considerably from soil salinity; as a consequence, reductions in germination, chlorophyll content, vigour and yield have been reported. Patel et al (2014) draw attention to interactions that occur with this species in the rhizosphere and report on those with halotolerant Bacillus spp. These species were isolated from saline habitats and alleviate salt stress in mung beans thereby increasing germination and partially restoring root and shoot growth.…”
mentioning
confidence: 99%